2023
DOI: 10.1155/2023/6711071
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Zinc Supplementation in Taste Disorder Treatment: A Systematic Review and Meta-Analysis of Randomized Controlled Trials

Abstract: Introduction. Food taste and flavour affect food choice and acceptance, which are essential to maintain good health and quality of life. Reduced circulating zinc levels have been shown to adversely affect the taste, but the efficacy of zinc supplementation to treat disorders of taste remains unclear. In this systematic review and meta-analysis, we aimed to examine the efficacy of zinc supplementation in the treatment of taste disorders. Methods. We searched four electronic bibliographical databases: Ovid MEDLI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 36 publications
2
4
0
Order By: Relevance
“…The results of the present study are consistent with this information. Previous studies have indicated that poor nutritional status hinders healing of in ammation [29][30][31], consistent with the present ndings. Maintaining good nutritional status is crucial in chemotherapy administration.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The results of the present study are consistent with this information. Previous studies have indicated that poor nutritional status hinders healing of in ammation [29][30][31], consistent with the present ndings. Maintaining good nutritional status is crucial in chemotherapy administration.…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, low serum zinc levels are associated with dysgeusia [29], and albumin levels have been reported to correlate with serum zinc levels [30]. The results of the present study are consistent with this information.…”
Section: Discussionsupporting
confidence: 91%
“…However, the single tablet serving for this supplement contains only 5 mg of zinc, an amount significantly less than the recommended daily intake according to the British Obesity and Metabolic Surgery Society (BOMSS, 2020), which suggests that zinc should be consumed at a ratio of 8–15 mg per mg of copper [ 19 ]. The maximum daily zinc consumption that is unlikely to have a negative impact on health is 40 mg for those over 19 years of age [ 20 ], and the role of zinc in the support of taste and the development of taste buds has been well-established in the previous literature [ 21 , 22 ]. These facts, taken together, suggest that the current zinc supplementation prescribed in clinical practice is insufficient to avoid zinc deficiency and thus to help prevent taste change following MGB.…”
Section: Discussionmentioning
confidence: 99%
“…Zn also possesses antioxidant and anti-inflammatory properties that prevent damage to cells (28). Clinically, Zn supplementation is used for treating several infectious diseases, such as diarrhea, malaria, and COVID-19 (29). Of particular interest to many researchers is the fact that Zn is a nutrient required for maintaining a healthy sense of taste and smell (30).…”
Section: The Nutritional Roles Of Zn In Human Bodymentioning
confidence: 99%